Aquaculture and water resource management (Blackwell Science, 1996)
The increasing global importance of aquaculture as a food-producing activity is mirrored by the continuing decline in wild fish stocks. With this explosion in aquaculture production have come attendant environmental problems. Owing to its tight linkage with natural ecosystems, it can be argued that aquaculture has the potential to have a much more profound impact on environmental quality than terrestrial farming systems of equal size. Moreover, it can also be argued that to become sustainable, practioners of aquaculture must place more emphasis on recognising these linkages, and protecting the ecosystems which nuture and sustain their industry.